Origin of Perpendicular Magnetic Anisotropy in Yttrium Iron Garnet Thin Films Grown on Si (100) - (:unkn) unknown (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2020)
We report the magnetic properties of yttrium iron garnet (YIG) thin films grown by pulsed laser deposition technique. The films were deposited on Si (100) substrates in the range of 15-50 nm thickness. Magnetic characterizations were investigated by ferromagnetic resonance spectra. Perpendicular magnetic easy axis was achieved up to 50 nm thickness. We observed that the perpendicular anisotropy values decreased by increasing the film thickness. The origin of the perpendicular magnetic anisotropy (PMA) was attributed to the texture and the lattice distortion in the YIG thin films. We anticipate that perpendicularly magnetized YIG thin films on Si substrates pave the way for a cheaper and compatible fabrication process.
Keywords: Ferromagnetic resonance (FMR); perpendicular magnetic anisotropy (PMA); yttrium iron garnet (YIG); FERROMAGNETIC-RESONANCE